Manajemen Rekrutmen Tenaga Pendidik Dalam Penguatan Kualitas Sumber Daya Manusia - Badi’atul Qomah; Moh. In’am Jamaluddin; Abu Darim; Imam Syafi’I; Juli Amaliya Nasucha (Pedir Research Institute, 2022)
The recruitment process is very important to obtain an effective recruitment result. Recruitment is carried out according to the needs of the school. This study is aimed to analyze the planning, organization, and implementation of the recruitment of educators in strengthening the quality of human resources at SMP-IT Hikmatul Ummah Mojosari. This research belongs to qualitative research with a field research approach. The data collected are in the form of primary data obtained from primary sources and secondary data obtained from other parties. The data were collected through interviews, observation, and documentation methods. The data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. The results of this study indicated that the planning, organization and implementation of the recruitment of educators at SMP-IT Hikmatul Ummah Mojosari were carried out by the Curriculum Department after receiving approval from the principal and the foundation. The information dissemination utilizes social media and family networks which were based on the principle of recruiting educators objectively by considering several aspects of the requirements: the national education standards about teaching staff and the standards set by the institution.